Comparative Anthropometric Circumferential Measurement of Yoruba and Igbo Ethnic Groups in Nigeria - , Lekpa Kingdom David; , Peter Done Okoh; , Hakeem Babatunde Fawehinmi; , Loveday Ese Oghenemavwe; , Chile Augustine Oparaocha; , Celestine Ebieto Ebieto; , Michael Anozie Amadi; , Faustina Chiamaka Irozulike (Archives of Current Research International, 2025)
Background: Circumferential measurements are important in various fields, including healthcare, sports, and industry. They are widely used to assess obesity levels, determine body fat distribution, and monitor changes in body composition over time. Aim: This study compared the circumferential body measurements of Yoruba and Igbo individuals. Methods: The cross-sectional descriptive research design was adopted in this study. 800 subjects (400 Yoruba and 400 Igbo) were recruited between 18 and 40 years. Data analysis was done using the International Business Machine of the Statistical Package for Social Science (IBM version 23). Descriptive Statistics were presented, and an independent T-test was used to compare the mean among the ethnic groups. A probability less than 0.005 (p<0.005) was considered statistically significant, and 95% was the confidence level. Results: The anthropometric circumferential differences between the both ethnic groups shows that neck circumference were (35.61±2.78cm, 31.69±2.37cm), mid-arm circumference were (27.87±3.28cm, 26.99±3.52cm), chest circumference were (85.64±5.74cm, 84.83±5.25cm), waist circumference were (75.99±7.49cm, 75.68±9.34cm), hip circumference were (89.86±5.25cm, 92.13±5.42cm), and mid-thigh were (49.05±5.58cm, 52.19±5.98cm) in Yoruba and Igbo respectively. It shows all parameters were statistically significant except chest and waist circumferences, which were not significant (p<0.005). Conclusion: The Yoruba and Igbo ethnic groups show slight variations in body measurements. These findings highlight that while both ethnic groups have comparable body proportions, minor differences may arise due to genetic diversity, environmental influences, and individual lifestyle variations.